Designing a 6G testbed for location: Use cases, challenges, enablers and Requirements - Khatib, Emil Jatib; Álvarez-Merino, Carlos Simón; Luo Chen, Hao Qiang; Barco-Moreno, Raquel (IEEE Xplore, 2023)
Location will have a central role in Research and Development (R&D) towards 6G networks, both as a service offered by the network (improving the current offering of 5G) and as an input to increasingly location-aware services and network functions. To integrate location into 6G standards, it will be very important to design validation systems such as testbeds, even when the actual technology is not yet commercially available. This paper performs a review of the use cases and their requirements, enabling technologies in 6G, and challenges; and proposes a flexible testbed architecture for performing network location related R&D. This architecture will allow to deploy an evolving infrastructure which will allow early validation of 6G technologies.
Keywords: Telecomunicaciones; Testbed; Proof-of-concept; Beyond fifth generation (5G); Sixth generation (6G); Location; Indoor positioning